Sapientia - Anidjar, Gil (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Gil Anidjar Title (English): Sapientia Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 102-103 Page Count: 2 Citation (English): Gil Anidjar, “Sapientia,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 102-103.